Smart Health Village in Improving Disaster Preparedness - Ardhiles Wahyu Kurniawan; Ratna Roesardhyati; Apriyani Puji Hastuti; Risky Siwi Pradini; Ambarika, Rahmania (Journal Of Nursing Practice, 2024)
Background: Disaster-prone areas are areas that have the potential for natural disasters such as earthquakes, mountain eruptions, landslides caused by activity or movement from the base of the earth. Understanding the potential for natural disasters in each region as one of the anticipatory steps to minimize the number of victims of natural disasters. Precise and accurate information is needed for disaster management. The slope of the area is quite steep, and road access to villages and tourist attractions is vulnerable to landslides. The current disaster incident information reporting system still applies the conventional model. The community also experiences difficulties in receiving information and submitting reports regarding village conditions. Purpose: This research aims to analyze the effectiveness of smart health villages in improving disaster preparedness. Method: The research design used a pre-experiment with a pre-test and post-test design approach with a sample size of 64 volunteers who were taken using purposive sampling. The independent variable in this study is Smart Health Village and the dependent variable is the voluntary task force's ability to preparedness disaster. The research instrument used a questionnaire for each variable. Data analysis in this study is the Wilcoxon Signed Rank Test. The implementation of this activity consists of the design stage, application creation, system design, socialization and training, and trial. Results: The research results showed that the voluntary task force's preparedness was in a good category as much as 88% and as enough as 12% with p value = 0.000. This application system smart health village based on the web allows both the community (users), admin (task force), and verifiers (village officials) to access anywhere and at any time, thus increasing the capability and quality of human resources in disaster preparedness and disaster-prone areas. Conclusion: Based on the results it can be concluded that smart health village can improve ability in preparedness of disaster in disaster- prone areas thus reducing impact of anxiety and and panic due to disaster.